UPAYA PENGEMBANGAN MATERI AJAR TEKS REKON FASE E BERBANTUAN AUGMENTED REALITY - Chairun Nisa; Hutagalung, Trisnawati (PT. CASA CENDEKIA MEDIA, 2024)
This research aims to develop teaching materials for phase E recount texts assisted by augmented reality in high school using Brog and Gall development research procedures. Subjects This research consists of material expert validators, media expert validators, design expert validators and Indonesian language subject teachers at Nurul Islam Indonesia High School. Data collection techniques used in this development research are documentation to analyze teaching materials, interviews to find out problems in learning and questionnaires to validate to find out the problems in learning and questionnaires to validate the developed product. The results of this study indicate that the teaching materials augmented reality-assisted recount text teaching materials that have been developed are in the in very good qualifications / very feasible with a value of 90.6% from material expert validators, validators of 90.6%, media expert validators of 88.3%, design expert validators of 92.5% and subject matter teachers of 95.5%. Based on the assessment. The final result of the average feasibility of the material developed is 91.7% with very good / very feasible qualifications so that it can be drawn conclusion that the teaching material for recount text assisted by augmented Reality teaching materials developed are very feasible to use during learning.